Combinatorial functional and differential equations applied to differential posets - Menni, Matías (2008)
We give combinatorial proofs of the primary results developed by Stanley for deriving enumerative properties of differential posets. In order to do this we extend the theory of combinatorial differential equations developed by Leroux and Viennot.